DEVELOPMENT AND VALIDATION OF STABILITY INDICATING REVERSE PHASE HIGH‑PERFORMANCE LIQUID CHROMATOGRAPHIC METHOD FOR THE ESTIMATION OF PIRIBEDIL IN BULK DRUG - KBV, ROHITH; Ramana G, Venkata; Latha N, Madhavi; P, Supriya; U, Harini; Akm, Pawar (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: A simple, precise, fast, economic, accurate, robust, and stability indicating isocratic reverse phase high-performance liquid chromatographic method was developed for the analysis of Piribedil. Method: The chromatographic conditions were standardized using Unisol C-18 (4.6 × 150 mm × 3.0 μ) column with UV detection at 244 nm, and the mobile phase composed of methanol:acetate buffer-pH 5.0 (85:15, v/v). Results: The retention time of Piribedil was found to be 3.4 minutes. The calibration curve was linear with correlation coefficient of 0.999 over a concentration range of 20-100 μg/ml with linear regression equationy=74,69,224.37x−39,46,924.90. The limit of detection and limit of quantitation were found to be 0.04 and 0.4 μg/ml, respectively. Conclusion: The proposed method has been validated according to the ICH guidelines. Piribedil was subjected to stress conditions including acidic, alkaline, oxidation, photolysis, and thermal degradation. Piribedil is more sensitive to photolytic stress. There are no interfering peaks from degradation products at analyte retention time, and thus the method is specific for the estimation of Piribedil in the presence of degradation products. Thus, the proposed method can be successfully applied in the routine quality control and stability samples of Piribedil in bulk drug. Keywords: Piribedil, Validation, Stability indicating, Reverse phase high-performance liquid chromatographic.